2014
DOI: 10.1208/s12248-014-9599-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Reporting of the Clinical Immunogenicity of Therapeutic Proteins and Peptides—Harmonized Terminology and Tactical Recommendations

Abstract: Abstract. Immunogenicity is a significant concern for biologic drugs as it can affect both safety and efficacy. To date, the descriptions of product immunogenicity have varied not only due to different degrees of understanding of product immunogenicity at the time of licensing but also due to an evolving lexicon that has generated some confusion in the field. In recent years, there has been growing consensus regarding the data needed to assess product immunogenicity. Harmonization of the strategy for the eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
267
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(271 citation statements)
references
References 38 publications
4
267
0
Order By: Relevance
“…This analysis provides sufficient evidence to support long-term lack of immunogenicity of commercial eculizumab in the treatment of PNH [8]. Moreover, these findings are consistent with shorterterm studies in which HAHAs were infrequent, occurring in 2% (3/196) of patients [9].…”
Section: Assessment Of Human Antihuman Antibodies To Eculizumab Aftersupporting
confidence: 85%
“…This analysis provides sufficient evidence to support long-term lack of immunogenicity of commercial eculizumab in the treatment of PNH [8]. Moreover, these findings are consistent with shorterterm studies in which HAHAs were infrequent, occurring in 2% (3/196) of patients [9].…”
Section: Assessment Of Human Antihuman Antibodies To Eculizumab Aftersupporting
confidence: 85%
“…Each offers unique advantages (as discussed in "ADA DOMAIN SPECIFICITY STRATEGY"), and diverse approaches have been followed to assess and describe immunogenicity data for different ADC molecules (see Table I). A recent white paper suggests harmonized definitions and terminology to describe product immunogenicity (2). A similar effort may eventually come about with regard to immunogenicity assessment for ADCs.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, sponsor organizations are tasked with monitoring the immunogenicity of their therapeutic proteins and providing a thorough evaluation of this information to clinicians in the product label. This may include information on ADA prevalence and the impact of ADA on clinical safety and efficacy (2).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that clinical studies reported in the literature and conducted by individual institutions often relied on in-house assay methods for measuring not only the ADA but also the drug concentrations. A cross-study comparison of immunogenicity data in the literature may not be as informative as within-study comparisons because the immunogenicity results are highly dependent on the assay methodology used (3,9). As such, almost all prescribing information of biological products cautioned that comparison of incidence of ADA across products may be misleading.…”
Section: Introductionmentioning
confidence: 99%